Urinary Tract Infection in Term Neonates with Prolonged Jaundice - Pashapour, Nader; Nikibahksh, Ahmad Ali; Golmohammadlou, Sariyeh (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The aim of this study was to evaluate the frequency of urinary tract infection (UTI) in neonates with prolonged jaundice. Materials and Methods: Newborn infants with jaundice lasted more than 2 weeks were included in this study. Patients who had other signs or symptoms were excluded. Workup of prolonged hyperbilirubinemia was performed, including direct Coombâ€™s test, blood group of the neonate and the mother, complete blood count, blood smear, glucose-6-phosphate dehydrogenase (G6PD), reticulocyte count, serum level of bilirubin (unconjugated and conjugated), thyroid function tests (serum thyroxine [T4] and thyroid-stimulating hormone), urinalysis, and suprapubic urine culture. Pediatric nephrologists carried out further investigation including kidney function tests, renal ultrasonography, voiding cystourethrography, and Technetium Tc 99m dimercaptosuccinic acid renal scintigraphy for patients with a positive urine culture for microorganisms. Results: Of 100 neonates who were evaluated, 43 were boys and 57 were girls. All of the neonates were breastfed. Six suffered from UTI (4 boys and 2 girls). Reflux was detected on voiding cystourethrography in 1 and cortical defect in the kidney on renal scan in 2 boys. Conclusion: In our region, with a high rate of breastfeeding, UTI remains as an important cause of prolonged jaundice. Despite the high rate of urogenital system abnormality accompanied by neonatal UTI, there was not a significant difference between the signs and symptoms of jaundice in patients with and without UTI. Performing urine cultures should be considered as a routine procedure in the evaluation of every infant with prolonged jaundice.